Tourism and Hospitality Education in Universiti Malaysia : an entrepreneurial approach - Mohd Fadil Mohd Yusof; Ghazali Ahmad (2011)
The offering of tourism and hospitality education program in Malaysia is growing tremendously. Many higher learning institutions from the public and private education sector offer various tourism and hospitality management program specializing in different areas such as hotel, culinary, tour and travel and event management. The proliferation of these tourism and hospitality management programs creates heavy competition among these institution in attracting students for the program . However, there are not many studies conducted in examining the content of those programs as well as the strength and weaknesses. Therefore, this paper highlights the new development of tourism and hospitality education program currently offered by the University Malaysia Kelantan (UMK) and explain how those programs differ from the other higher learning institutions. As one of the public universities in Malaysia, UMK is focusing on the entrepreneurial education which includes tourism and hospitality as one of the area of specializations. In this paper, the content of the programs will be looked into as well as the teaching approach.